Exploring the landscape of symptom-specific inflammatory cytokines in post-COVID syndrome patients - Chafik Tilikete; Imen Zamali; Zeineb Meddeb; Ghassen Kharroubi; Soumaya Marzouki; Tarak Dhaouadi; Ahlem Ben Hmid; Samar Samoud; Yousr Galai; Selma Charfeddine; Leila Abid; Salem Abdessalem; et al. (BMC Infectious Diseases)
Abstract Introduction Post-COVID syndrome (PCS) is characterized by a polymorphism of symptoms with hypothetical pathophysiological mechanisms. Here, we aimed to analyze the profile of inflammatory cytokines in patients with PCS and to study the relationship between this profile, the clinical symptoms as well as the endothelial function in PCS. Methods Our analytical study involved all eligible patients (n = 66) with PCS included from April 2021 to December 2021. The serum concentration of cytokines IFN-γ, IL-1α, IL-1β, IL-6, IL-8, IL-10, IL-12p70, IL-27, IP-10, MCP-1 and TNF-α was quantified by flow cytometry. Endothelial function was explored by assessing microvascular flow and reactivity using thermal probes. A comparative study was carried out according to the presence of each PCS symptom. Results The average age of our patients was 55.9 ± 16.2 years. The sex ratio was 0.69. Forty-one patients (62%) presented with a severe form of acute infection. The most frequently reported symptoms were dyspnea (67%), fatigue (50%), and memory problems (32%). Fifty-seven patients (86%) had endothelial dysfunction. The majority of patients had increased levels of IP-10 (100%), IL-8 (95%), IFN-γ (95%), MCP-1 (80%), and TNF-α (70%). The serum concentration of IL-10 was below the threshold of quantification in 89% of subjects. The severe form of acute infection was associated with elevated IL-10, MCP-1, and IL-27. Increased IL-6 and IL-27 levels were associated with fatigue while IL-8 concentrations were higher in patients who reported dyspnea. Elevation of IL-8 level was more common in patients with profound impairment of endothelial function. Conclusion Our results further support the presence of endothelial dysfunction in PCS and show an elevation of pro-inflammatory cytokines with a downmodulation of the IL-10- anti-inflammatory response. In addition, immuno-clinical phenotypes emerge, such as an inflammatory profile mediated by IL-6 and IL-27 in fatigue and IL-8 in dyspnea. The identification of immuno-clinical phenotypes would allow a better understanding of the pathophysiology of PCS symptoms.